Existence Woman In Gathering Moon Short Story In On Lovina Work Yvonne De Fretes - Kadek Sintya Purnama Dewi; Jalu Norva Illa Putra (Yayasan Baru Haji Samsudin, 2025)
This study aims to examine the existence of women in the short story collection Bulan di Atas Lovina by Yvonne De Fretes through the lens of existentialist feminism. The research employs a literature study method, utilizing data collection techniques such as reading, note-taking, and textual documentation. A descriptive approach was applied to analyze and interpret the findings, focusing on the portrayal of women’s autonomy, freedom, and personal choices within the narrative.The analysis reveals that the short stories depict women as working individuals who maintain independence while experiencing love, reflecting the balance between personal freedom and emotional attachment. Furthermore, the study identifies both explicit messages, which are directly communicated through narrative elements, and implicit messages, which are embedded in character interactions, plot developments, and underlying themes. These messages highlight women’s struggles, self-determination, and empowerment in the context of contemporary society.Overall, the findings demonstrate that Yvonne De Fretes’ short stories provide a nuanced representation of women’s existence, emphasizing autonomy, self-realization, and agency, in alignment with existentialist feminist theory. This research contributes to a deeper understanding of women’s roles and experiences in literature, offering insights into the complexities of female identity, freedom, and empowerment